Does continuous electroencephalography influence therapeutic decisions in neurocritical care?. (11th November 2020) - Holm‐Yildiz, Sonja; Richter Hansen, Julie; Thonon, Vanessa; Beniczky, Sándor; Fabricius, Martin; Sidaros, Annette; Kondziella, Daniel
Abstract : Objectives: In the neurocritical care unit (neuro‐ICU), the impact of continuous EEG (cEEG) on therapeutic decisions and prognostication, including outcome prediction using the Status Epilepticus Severity Score (STESS), is poorly investigated. We studied to what extent cEEG contributes to treatment decisions, and how this relates to clinical outcome and the use of STESS in neurocritical care. Methods: We included patients admitted to the neuro‐ICU or neurological step‐down unit of a tertiary referral hospital between 05/2013 and 06/2015. Inclusion criteria were ≥20 h of cEEG monitoring and age ≥15 years. Exclusion criteria were primary epileptic and post‐cardiac arrest encephalopathies. Results: Ninety‐eight patients met inclusion criteria, 80 of which had status epilepticus, including 14 with super‐refractory status. Median length of cEEG monitoring was 50 h (range 21–374 h). Mean STESS was lower in patients with favorable outcome 1 year after discharge (modified Rankin Scale [mRS] 0–2) compared to patients with unfavorable outcome (mRS 3–6), albeit not statistically significant (mean STESS 2.3 ± 2.1 vs 3.6 ± 1.7, p = 0.09). STESS had a sensitivity of 80%, a specificity of 42%, and a negative predictive value of 93% for outcome. cEEG results changed treatment decisions in 76 patients, including escalation of antiepileptic treatment in 65 and reduction in 11 patients. Conclusion: Status Epilepticus Severity Score had a high negative predictive value but low sensitivity, suggesting that STESS should be used cautiously. Of note, cEEG results altered clinical decision‐making in three of four patients, irrespective of the presence or absence of status epilepticus, confirming the clinical value of cEEG in neurocritical care.